Energy partitioning on the photolysis and pyrolysis of diazirines - Van der Merwe, S. W. J.(Schalk Willem Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1974.